Elevated expression levels of lysyl oxidases protect against aortic aneurysm progression in Marfan syndrome. (August 2015) - Busnadiego, O.; Gorbenko del Blanco, D.; González-Santamaría, J.; Habashi, J.P.; Calderon, J.F.; Sandoval, P.; Bedja, D.; Guinea-Viniegra, J.; Lopez-Cabrera, M.; Rosell-Garcia, T.; Snabel, J.M.; Hanemaaijer, R.; et al.
Abstract: Patients with Marfan syndrome (MFS) are at high risk of life-threatening aortic dissections. The condition is caused by mutations in the gene encoding fibrillin-1, an essential component in the formation of elastic fibers. While experimental findings in animal models of the disease have shown the involvement of transforming growth factor-β (TGF-β)- and angiotensin II-dependent pathways, alterations in the vascular extracellular matrix (ECM) may also play a role in the onset and progression of the aortic disease. Lysyl oxidases (LOX) are extracellular enzymes, which initiates the formation of covalent cross-linking of collagens and elastin, thereby contributing to the maturation of the ECM. Here we have explored the role of LOX in the formation of aortic aneurysms in MFS. We show that aortic tissue from MFS patients and MFS mouse model ( Fbn1 C1039G/+ ) displayed enhanced expression of the members of the LOX family, LOX and LOX-like 1 (LOXL1), and this is associated with the formation of mature collagen fibers. Administration of a LOX inhibitor for 8 weeks blocked collagen accumulation and aggravated elastic fiber impairment, and these effects correlated with the induction of a strong and rapidly progressing aortic dilatation, and with premature death in the more severe MFS mouse model, Fbn1 mgR/mgR, without any significant effect on wild type animals. This detrimental effect occurred preferentially in the ascending portion of the aorta, with little or no involvement of the aortic root, and was associated to an overactivation of both canonical and non-canonical TGF-β signaling pathways. The blockade of angiotensin II type I receptor with losartan restored TGF-β signaling activation, normalized elastic fiber impairment and prevented the aortic dilatation induced by LOX inhibition in Fbn1 C1039G/+ mice. Our data indicate that LOX enzymes and LOX-mediated collagen accumulation play a critical protective role in aneurysm formation in MFS. Graphical abstract: Highlights: Lysyl oxidases are upregulated in the aorta of Marfan syndrome patients and mice. Lysyl oxidase inhibition disrupted collagen accumulation in Marfan mice. Lysyl oxidase inhibition aggravated elastic fiber impairment in Marfan mice. Lysyl oxidase inhibition induced ascending aorta dilatation in Marfan mice. Transforming growth factor-β signaling is potentiated by lysyl oxidase inhibition.